2016
DOI: 10.1038/srep38506
|View full text |Cite
|
Sign up to set email alerts
|

Robust increase in extreme summer rainfall intensity during the past four decades observed in China

Abstract: Global warming increases the moisture holding capacity of the atmosphere and consequently the potential risks of extreme rainfall. Here we show that maximum hourly summer rainfall intensity has increased by about 11.2% on average, using continuous hourly gauge records for 1971–2013 from 721 weather stations in China. The corresponding event accumulated precipitation has on average increased by more than 10% aided by a small positive trend in events duration. Linear regression of the 95th percentile daily preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 35 publications
4
59
0
Order By: Relevance
“…However, they also show a decreasing trend in North China and Southwest China. The results are consistent with the results of Xiao et al () and Gu et al (). Donat et al () found more extreme precipitation occurred in the world's dry and wet regions.…”
Section: Discussionsupporting
confidence: 93%
“…However, they also show a decreasing trend in North China and Southwest China. The results are consistent with the results of Xiao et al () and Gu et al (). Donat et al () found more extreme precipitation occurred in the world's dry and wet regions.…”
Section: Discussionsupporting
confidence: 93%
“…For China, Zhai et al [7] found that there is a small trend in total precipitation for China as a whole, but there are distinctive regional and seasonal patterns of trends, and there is a great similarity between the spatial patterns of trends in extreme and total precipitation. Xiao et al [8] found that the regionally averaged maximum summer hourly rainfall rate across a large part of China has increased by 11.2%, using continuous hourly gauge records for 1971-2013 from 721 weather stations in China. Liu et al [9] analyzed the trends of extreme precipitation in eastern China and their possible causes, and demonstrated that global warming was the primary cause of the changes in precipitation extremes, although a number of recent studies suggested that aerosols have huge effects on precipitation extremes.…”
Section: Introductionmentioning
confidence: 99%
“…In China, extreme climate events have exerted profound impacts on both human societies, natural environment and other industrial and agricultural sectors (Zhai et al 2005, Sun and Ding 2010, Ye 2014, Xiao et al 2016, Chen and Sun 2017. Over the past decades, a number of extreme climate events have caused large losses of life and tremendous economic losses.…”
Section: Introductionmentioning
confidence: 99%